Influence of Leadership Style and Work Motivation on Employee Productivity of Employees in PT. Asiatek Solution Indonesia - Kusnadi Kusnadi; Rizki Yulianti; Suseno Hadi Purnomo (Business and Entrepreneurial Review, 2020)
This study aimed to analyze the effect of leadership style and work motivation on employee work productivity of PT. Asiatek Solusi Indonesia. The population in this study was 230 permanent employees, the number of samples could be taken 30% of the total population so there were 69 employees as the total sample. The sampling technique uses the nonprobability sampling method. Methods of collecting primary data in the form of a questionnaire using Likert scale with questionnaire. Testing the validity and reliability using total Pearson product moment test and Cronbach Alpha. The method of analysis to answer the hypothesis using multiple linear regression with SPSS 22 version. The results showed that the leadership style and work motivation variables were significantly positive effect on the work productivity of employees of PT. Asiatek Solusi Indonesia amounted by 0,608 and 0,157. Variable of leadership style and work motivation simultaneously have a significant positive effect on productivity of employees PT. Asiatek Solusi Indonesia.